Human-carnivore relations: A systematic review. (September 2019) - Lozano, Jorge; Olszańska, Agnieszka; Morales-Reyes, Zebensui; Castro, Antonio A.; Malo, Aurelio F.; Moleón, Marcos; Sánchez-Zapata, José A.; Cortés-Avizanda, Ainara; von Wehrden, Henrik; Dorresteijn, Ine; Kansky, Ruth; Fischer, Joern; et al.
Abstract: We conducted a systematic review of 502 articles, published between 2000 and 2016, to characterize the research on human-carnivore relations according to (i) temporal and geographical distribution, (ii) biology, (iii) relations between carnivores and humans, (iv) social actors, (v) drivers of change, (vi) management, and (vii) applied methods. We performed a detrended correspondence analysis and Kruskal-Wallis tests to identify and describe thematic clusters used in human-carnivore relations research. Our results show that research is deeply biased so far, and four important knowledge gaps were detected. First, we found more studies had been conducted in the Global North than in the Global South, although risks and benefits of living alongside carnivores exist in the Global South equally. Second, most research focused on large predators, while small and medium-sized carnivores are also source of damages and ecosystem services. Third, relations were often framed around conflicts, with little attention to possible ecosystem services. Fourth, most research was carried out using natural sciences methods, despite methods from the social sciences having much to offer in this context. Research fell into seven thematic clusters focusing on: (1) North-American bears, (2) African large carnivores, (3) social research in America, (4) meso-carnivores, (5) Asian felids, (6) conflicts with the grey wolf, and (7) damages to human property. These results highlight the need for more integrative, social-ecological research on human-carnivore relations. We discuss how addressing existing knowledge gaps could contribute to mitigating conflicts as well as fostering coexistence between humans and carnivore species. Highlights: We systematically reviewed 17 years of human-carnivore relations research Human-carnivore relations research is geographically and taxonomically biased Small and middle-sized carnivores require more scientific attention globally Ecosystem services provided by carnivores need to be urgently studied Research needs to apply interdisciplinary social-ecological approaches